Blood Cancer Cell Classification based on Geometric Mean Transform and Dissimilarity Metrics - Kahaki, SMM; Nordin, MJ; Zahra, SJ; Hassan, R; Waidah Ismail (Univ Putra Malaysia Press, 2024)
Indexed by Scopus/ERA